A quasi-experimental study of the differences in performance and clinical reasoning using individual learning versus reciprocal peer coaching - Ladyshewsky, Richard (Taylor and Francis, 2002)
Peer assisted learning such as Reciprocal Peer Coaching (RCP) is being used more frequently in the clinical education of physiotherapists. The efficacy of this learning approach on clinical performance and reasoning, however, has not been evaluated with much rigour. The purpose of this research is to measure the impact of this method on clinical performance and reasoning in two groups of students. One group examined a simulated patient (SP) individually. The other group examined the SP as a reciprocal peer coaching (RPC) dyad. Sixty-two third year physiotherapy students participated in this study. Twenty individual students and twenty-one dyads each evaluated a SP with shoulder pathology. Clinical performance and reasoning were measured. Students in the RPC group significantly outperformed their peers in the individual learning group in the categories of physical examination, communication, and clinical reasoning. The cognitive support that RPC provides novices during patient encounters is a valuable educational support tool. By incorporating more peer coaching in clinical education environments, it is possible to influence the clinical performance and reasoning of novices in a positive manner, thus enhancing the development of clinical competency.